Ultrafast photoinduced processes in subphthalocyanine electron donor-acceptor conjugates linked by a single B-N bond∥ - Nieto, Carlos Romero; Guilleme, Julia; Fernandez-Ariza, Javier; Salome Rodriguez-Morgade, M.; Gonzalez-Rodriguez, David; Torres, Tomas; Guldi, Dirk Michael (Organic Letters, 2012)
We have prepared two different subphthalocyanine conjugates by linking these macrocycles either to an electron-accepting perylene diimide or to an electron-donating phenothiazine through a single B-N covalent bond. The short spacing between the two active building blocks results in ultrafast photoinduced electron-transfer reactions. © 2012 American Chemical Society.